Исследование конверсии метана в ароматические углеводороды на катализаторах Ag-Mo/ZSM-5; Кинетика и катализ; Т. 52, вып. 3 - Восмериков А. В. Александр Владимирович; Зайковский В. И. Владимир Иванович; Коробицына (Кузнецова) Л. Л. Людмила Леонидовна; Козлов В. В. Владимир Валерьевич; Арбузова Н. В. Нина Витальевна; Журавков С. П. Сергей Петрович (2011, 2011)
Заглавие с экрана